Southwest Research-Extension Center, Field Day 1991 (Kansas Agricultural Experiment Station Research Reports, 1991)
Report of agricultural research from Southwest Research-Extension Center of Kansas State University.
Keywords: 1991; SRP630; crops; tillage; irrigation; insect control